DIGITAL MARKETING STRATEGY ON INSTAGRAM SOCIAL MEDIA FOR MICRO, SMALL AND MEDIUM BUSINESS IN BAGHDAD - Israa Natiq Jabbar (Scientia integritas Utama, 2022)
Digital marketing has been proven as an effective way to expand brand reach and increase sales figures. Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the internet, including the activities of Micro, Small and Medium Enterprises in utilizing information technology to run their business. The purpose of this research is to generally describe the impact of digital marketing on sales volume for MSEs in the city of Baghdad. The method used in this research is descriptive qualitative, where the researcher tries to describe and analyze specifically the data obtained in the field according to the focus of the problem to be studied. The results of this study indicate that selecting the right social media platforms and good content management can increase sales. Utilization of Instagram social media has a positive impact on the development of product marketing so that Instagram followers and sales increase. Apart from that, the operation is easy and there are many users so that it becomes a practical promotional medium, which is cheap, reliable and can reach all users wherever they are.